Iodination of carbohydrate-derived 1,2-oxazines to enantiopure 5-iodo-3,6-dihydro-2H-1,2-oxazines and subsequent palladium-catalyzed cross-coupling reactions - Medvecký, Michal; Linder, Igor; Schefzig, Luise; Reissig, Hans-Ulrich; Zimmer, Reinhold (Beilstein Journal of Organic Chemistry, 2016)
Iodination of carbohydrate-derived 3,6-dihydro-2H-1,2-oxazines of type 3 using iodine and pyridine in DMF furnished 5-iodo-substituted 1,2-oxazine derivatives 4 with high efficacy. The alkenyl iodide moiety of 1,2-oxazine derivatives syn-4 and anti-4 was subsequently exploited for the introduction of new functionalities at the C-5 position by applying palladium-catalyzed carbon–carbon bond-forming reactions such as Sonogashira, Heck, or Suzuki coupling reactions as well as a cyanation reaction. These cross-coupling reactions led to a series of 5-alkynyl-, 5-alkenyl-, 5-aryl- and 5-cyano-substituted 1,2-oxazine derivatives being of considerable interest for further synthetic elaborations. This was exemplarily demonstrated by the hydrogenation of syn-21 and anti-24 and by a click reaction of a 5-alkynyl-substituted precursor.
Keywords: amino alcohol; click reaction; cross-coupling reactions; hydrogenation; iodination; 1,2-oxazines

(untitled) - Brasholz, M.; Reissig, H.-U.; Zimmer, R. (Acc. Chem. Res., 2009)

(untitled) - Zimmer, R.; Reissig, H.-U. (Chem. Soc. Rev., 2014)

(untitled) - Schade, W.; Reissig, H.-U. (Synlett, 1999)

(untitled) - Helms, M.; Schade, W.; Pulz, R.; Watanabe, T.; Al-Harrasi, A.; Fišera, L.; Hlobilová, I.; Zahn, G.; Reissig, H.-U. (Eur. J. Org. Chem., 2005)

(untitled) - Al-Harrasi, A.; Fischer, S.; Zimmer, R.; Reissig, H.-U. (Synthesis, 2010)

(untitled) - Pulz, R.; Al-Harrasi, A.; Reissig, H.-U. (Org. Lett., 2002)

(untitled) - Dekaris, V.; Reissig, H.-U. (Synlett, 2010)

(untitled) - Dekaris, V.; Pulz, R.; Al-Harrasi, A.; Lentz, D.; Reissig, H.-U. (Eur. J. Org. Chem., 2011)

(untitled) - Jasiński, M.; Lentz, D.; Reissig, H.-U. (Beilstein J. Org. Chem., 2012)

(untitled) - Jasiński, M.; Moreno-Clavijo, E.; Reissig, H.-U. (Eur. J. Org. Chem., 2014)

(untitled) - Jasiński, M.; Utecht, G.; Fruziński, A.; Reissig, H.-U. (Synthesis, 2016)

(untitled) - Parmeggiani, C.; Cardona, F.; Giusti, L.; Reissig, H.-U.; Goti, A. (Chem. – Eur. J., 2013)

(untitled) - Jasiński, M.; Watanabe, T.; Reissig, H.-U. (Eur. J. Org. Chem., 2013)

(untitled) - Al-Harrasi, A.; Bouché, L.; Zimmer, R.; Reissig, H.-U. (Synthesis, 2011)

(untitled) - Bouché, L.; Reissig, H.-U. (Pure Appl. Chem., 2012)

(untitled) - Bouché, L.; Kandziora, M.; Reissig, H.-U. (Beilstein J. Org. Chem., 2014)

(untitled) - Bouché, L.; Reissig, H.-U. (Eur. J. Org. Chem., 2014)

(untitled) - Kandziora, M.; Reissig, H.-U. (Beilstein J. Org. Chem., 2014)

(untitled) - Kandziora, M.; Reissig, H.-U. (Eur. J. Org. Chem., 2015)

(untitled) - Kandziora, M.; Mucha, E.; Zucker, S. P.; Reissig, H.-U. (Synlett, 2015)

(untitled) - Dernedde, J.; Enders, S.; Reissig, H.-U.; Roskamp, M.; Schlecht, S.; Yekta, S. (Chem. Commun., 2009)

(untitled) - Roskamp, M.; Enders, S.; Pfrengle, F.; Yekta, S.; Dekaris, V.; Dernedde, J.; Reissig, H.-U.; Schlecht, S. (Org. Biomol. Chem., 2011)

(untitled) - Moinizadeh, N.; Klemme, R.; Kansy, M.; Zimmer, R.; Reissig, H.-U. (Synthesis, 2013)

(untitled) - Zimmer, R.; Schmidt, E.; Andrä, M.; Duhs, M.-A.; Linder, I.; Reissig, H.-U. (Beilstein J. Org. Chem., 2009)

(untitled) - Linder, I.; Gerhard, M.; Schefzig, L.; Andrä, M.; Bentz, C.; Reissig, H.-U.; Zimmer, R. (Eur. J. Org. Chem., 2011)

(untitled) - Zimmer, R.; Reissig, H.-U.; Homann, K. (J. Prakt. Chem., 1995)

(untitled) - Nubbemeyer, U. (Sci. Synth., 2008)

(untitled) - Sha, C.-K.; Shen, C.-Y.; Jean, T.-S.; Chiu, R.-T.; Tseng, W.-H. (Tetrahedron Lett., 1993)

(untitled) - Paintner, F. F.; Allmendinger, L.; Bauschke, C. (Synlett, 2005)

(untitled) - Hanessian, S.; Focken, T.; Oza, R. (Org. Lett., 2010)

(untitled) - Gwiazda, M.; Reissig, H.-U. (Synthesis, 2008)

(untitled) - Lechel, T.; Dash, J.; Brüdgam, I.; Reissig, H.-U. (Eur. J. Org. Chem., 2008)

(untitled) - Voigt, K.; von Zezschwitz, P.; Rosauer, K.; Lansky, A.; Adams, A.; Reiser, O.; de Meijere, A. (Eur. J. Org. Chem., 1998)

(untitled) - Lyapkalo, I. M.; Webel, M.; Reissig, H.-U. (Eur. J. Org. Chem., 2001)

(untitled) - Merlic, C. A.; Semmelhack, M. F. (J. Organomet. Chem., 1990)

(untitled) - Crestey, F.; Collot, V.; Stiebing, S.; Rault, S. (Synthesis, 2006)

(untitled) - Carlström, A.-S.; Frejd, T. (Synthesis, 1989)

(untitled) - Carlström, A.-S.; Frejd, T. (Acta Chem. Scand., 1992)

(untitled) - Arcadi, A.; Cacchi, S.; Marinelli, F.; Morera, E.; Ortar, G. (Tetrahedron, 1990)

(untitled) - Yokoyama, Y.; Takahashi, M.; Takashima, M.; Kohno, Y.; Kobayashi, H.; Kataoka, K.; Shidori, K.; Murakami, Y. (Chem. Pharm. Bull., 1994)

(untitled) - de Azambuja, F.; Duarte Correia, C. R. (Tetrahedron Lett., 2011)

(untitled) - Bozell, J. J.; Vogt, C. E.; Gozum, J. (J. Org. Chem., 1991)

(untitled) - Taszarek, M.; Reissig, H.-U. (ChemistrySelect, 2016)

(untitled) - Ajana, W.; Feliu, L.; Alvarez, M.; Joule, J. A. (Tetrahedron, 1998)

(untitled) - Miyaura, N.; Suzuki, A. (Chem. Rev., 1995)

(untitled) - Quirante, J.; Escolano, C.; Massot, M.; Bonjoch, J. (Tetrahedron, 1997)

(untitled) - Hübner, H.; Haubmann, C.; Utz, W.; Gmeiner, P. (J. Med. Chem., 2000)

(untitled) - Yamamura, K.; Murahashi, S.-I. (Tetrahedron Lett., 1977)

(untitled) - Piers, E.; Fleming, F. F. (Can. J. Chem., 1993)

(untitled) - Singh, M. S.; Chowdhury, S.; Koley, S. (Tetrahedron, 2016)

(untitled) - Wang, Q.; Chan, T. R.; Hilgraf, R.; Fokin, V. V.; Sharpless, K. B.; Finn, M. G. (J. Am. Chem. Soc., 2003)

(untitled) - Haldón, E.; Nicasio, M. C.; Pérez, P. J. (Org. Biomol. Chem., 2015)

(untitled) - Pulz, R.; Watanabe, T.; Schade, W.; Reissig, H.-U. (Synlett, 2000)